Energy - economic Growth Nexus Long Run and Causal Inference - John K. Njenga (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
There exists an economic relationship between energy consumption and economic growth. This chapter outlines the nature of linkage and direction of causal flow as the essential components of understanding the nexus between the two variables. Long-run analysis helps to understand how energy interacts at a level with economic growth.ARDL bound test for cointegration is preferred as it does have integration order limitations. Cointegration implies causality, causality does not imply cointegration. The Granger causality test is used to test for the nature and direction of causal links. The framework is applied to analyze the electricity consumption and economic growth relationship in a case study of Kenya.